The main agroecological structure, a methodology for the collective analysis of the Mediterranean agroecological landscape of San Clemente, Region del Maule, Chile - Salazar-Rojas, Angel; Castro-Huerta, Ricardo; Altieri, Miguel (Frontiers in Sustainable Food Systems, 2023)
The simplification of the landscape as a consequence of the decrease in biodiversity and the adoption of monoculture production systems has led to a significant decrease in the provision of ecosystem services in the territory. The conversion of agroecosystems requires the adoption of agroecological techniques, which aim to design the agroecosystem as an integrated part of a vegetation matrix of the landscape, interconnecting the different production systems with the agricultural landscape. In order to measure the degree of connectivity of agroecosystems with the landscape, we used the Main Agroecological Structure (MAS) method, which was applied to 36 small agroecosystems of vegetable, livestock and fruit producers, which generally presented a low degree of connectivity. This allows us to evaluate the potential of these systems for agroecological transition, since being present in a moderately complex agricultural landscape gives important advantages over a more simplified system, allowing these producers to dispense with the use of many energy subsidies. This evaluation allows a first approximation to the quantification of the landscape matrix and will allow a comparison between agroecosystems or an evaluation of the evolution of the MAS over time. It is necessary to complement the MAS by quantifying the ecosystem services that may be associated with it.